2021
DOI: 10.1017/s0144686x21001045
|View full text |Cite
|
Sign up to set email alerts
|

Asset-rich and cash-poor: which older adults value reverse mortgages?

Abstract: Home equity represents a substantial share of retirement wealth for many older persons, particularly in Asia where national housing policies have encouraged home-ownership. This paper explored the potential for reverse mortgages to help ‘asset-rich and cash-poor’ older Singaporeans unlock their home equity while ageing in place. The empirical analysis was based on a nationally representative survey of home-owners age 50+ in the 2018 Singapore Life Panel (N = 6,258). Our analyses showed that the average older h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The problem, however, is more complex as many older people are not aware of such options to increase their income. As Fong et al (2021) showed for Singapore, although an average older homeowner's wealth consists of housing equity in 60%, only 25% of older homeowners reports an interest in a commercial reverse mortgage. This means that the potential of a reversed mortgage is not used to increase retirement income.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The problem, however, is more complex as many older people are not aware of such options to increase their income. As Fong et al (2021) showed for Singapore, although an average older homeowner's wealth consists of housing equity in 60%, only 25% of older homeowners reports an interest in a commercial reverse mortgage. This means that the potential of a reversed mortgage is not used to increase retirement income.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Recent empirical works show that housing wealth gains in importance as a source of additional retirement income, including implicit rent, and it can be a relevant pillar supporting pension adequacy (Hu et al, 2020; Jaiyawala et al, 2022). On the other hand, some authors notice the unawareness of the older population in terms of the options to release the home equity in order to gain additional retirement income (Fong et al, 2021; Kim et al, 2021). That is why the use of housing wealth has an unexplored potential to reduce poverty among the elderly and support their consumption.…”
Section: Related Literaturementioning
confidence: 99%
“…The reverse mortgages program allows older homeowners to unlock and consume a portion of their home equity without leaving their properties (Boj et al, 2022;Fong et al, 2020). With reverse mortgages, the older homeowners may borrow from the lenders using their properties as collateral.…”
Section: Introductionmentioning
confidence: 99%